2007
DOI: 10.1130/g23106a.1
|View full text |Cite
|
Sign up to set email alerts
|

Bedrock channel adjustment to tectonic forcing: Implications for predicting river incision rates

Abstract: We present detailed data of channel morphology for a river undergoing a transient response to active normal faulting where excellent constraints exist on spatial and temporal variations in fault slip rates. We show that traditional hydraulic scaling laws break down in this situation, and that channel widths become decoupled from drainage area upstream of the fault. Unit stream powers are ~4 times higher than those predicted by current scaling paradigms and imply that incision rates for rivers responding to act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
392
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 276 publications
(415 citation statements)
references
References 18 publications
20
392
1
2
Order By: Relevance
“…Purely transport-limited behavior can be ruled out, given the shape of the long profiles (compare Figures 4 and 1). Stream morphology data also reveal the importance of dynamic adjustment in channel width (Whittaker et al, 2007a;Attal et al, 2008). The Central Apennines example illustrates the value of natural experiments in transient response for teasing out key elements of geomorphic behavior and discriminating between alternative models.…”
Section: Natural Experiments In Transient Topographymentioning
confidence: 99%
See 3 more Smart Citations
“…Purely transport-limited behavior can be ruled out, given the shape of the long profiles (compare Figures 4 and 1). Stream morphology data also reveal the importance of dynamic adjustment in channel width (Whittaker et al, 2007a;Attal et al, 2008). The Central Apennines example illustrates the value of natural experiments in transient response for teasing out key elements of geomorphic behavior and discriminating between alternative models.…”
Section: Natural Experiments In Transient Topographymentioning
confidence: 99%
“…For instance, some authors have found that a combination of field surveys and photogrammetric 10 m to 30 m resolution DEMs were sufficient (if not ideal) for studying stream incision (e.g. Snyder et al, 2000;Duvall et al, 2004;Whittaker et al, 2007a;Attal et al, 2008), while other applications require meter-to sub-meter, true-ground (not canopy) data of the sort that can be obtained with airborne or ground-based LiDAR (e.g. Roering et al, 1999;Roering, 2008).…”
Section: Ingredients Of a Natural Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…sure for channel width in which width scales as the square root of water discharge (e.g., Leopold and Maddock, 1953;Wohl and David, 2008), it may be desirable for some applications to add dynamic channel width adjustments to the model, as previous work has suggested that width trades off with slope in transient channels (e.g., Finnegan et al, 2005;Turowski et al, 2006;Wobus et al, 2006;Whittaker et al, 2007;Attal et al, 2008;Lague, 2010;Yanites and Tucker, 2010). One option for incorporating dynamic width is to calculate or approximate shear-stress distributions across channel cross sections (e.g., Kean and Smith, 2004;Wobus et al, 2006Wobus et al, , 2008Turowski et al, 2009).…”
Section: Entrainment Of Bed Sediment and Erosion Of Bedrockmentioning
confidence: 99%